PEMANFAATAN E-LEARNING E-LENA DALAM PENINGKATAN KUALITAS PEMBELAJARAN DASAR STATISTIKA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN ADMINISTRASI PERKANTORAN FAKULTAS EKONOMI UNNES - Muhsin, Muhsin; Ismiyati, Ismiyati (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
It is a pre-experiment study. The study used two classes, the first class was the treatment class using E-lena learning system and the second class was the control class without using E-lena learning system. The subject of this study was students of Office Administration of Economics Education Department, Economics Faculty, Semarang State University. The data were collected by test, and then analyzed by descriptive qualitative. The result of this study showed that using E-lena learning system could improve students’ self awareness in learning, but unfortunately the system still had some problems related to the application.